2023
DOI: 10.3390/onco3030011
|View full text |Cite
|
Sign up to set email alerts
|

NUP98 Rearrangements in AML: Molecular Mechanisms and Clinical Implications

Abstract: NUP98 fusions constitute a small subgroup of AML patients and remain a high-risk AML subtype. There are approximately 30 types of NUP98 fusions identified in AML patients. These patients show resistance to currently available therapies and poor clinical outcomes. NUP98 fusions with different fusion partners have oncogenic transformation potential. This review describes how the NUP98 gene acquires oncogenic properties after rearrangement with multiple partners. In the mechanistic part, the formation of nuclear … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
3
1

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 153 publications
0
3
0
Order By: Relevance
“…3C). While standard-of-care cytogenetics identified both KMT2A and NUP214 fusions, only CytoTerra identified the NUP98 fusion, a variant associated with poor outcomes(8). In this case, CytoTerra offers benefit in identifying variants of import over existing standard methods.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…3C). While standard-of-care cytogenetics identified both KMT2A and NUP214 fusions, only CytoTerra identified the NUP98 fusion, a variant associated with poor outcomes(8). In this case, CytoTerra offers benefit in identifying variants of import over existing standard methods.…”
Section: Discussionmentioning
confidence: 99%
“…These variants included a NUP98::KDM5A fusion created by a t(11;12)(p15.4;p13.33), a variant associated with poor prognosis and chemoresistance (Fig. 3D) (8) . This rearrangement was not previously detected in the cytogenetics report for this patient.…”
Section: E Detection Of Inter-chromosomal and Intrachromosomal Rearra...mentioning
confidence: 99%
“…NUP98 fusions typically portend poor prognosis and may be associated with chemotherapy resistance [ 67 , 68 ]. Like MLL fusion and NPM1 mutations, NUP98 fusion proteins bind to chromatin near HOX genes resulting in their overexpression through a number of different mechanisms, including altered DNA methylation and acetylation [ 69 ]. The binding of NUP98 fusion genes to chromatin is dependent on both MLL and Menin, and in preclinical studies, leukemic cells harboring NUP98 fusions were shown to respond to Menin inhibition [ 70 ].…”
Section: Meninmentioning
confidence: 99%